The free word order phenomenon : its syntactic sources and diversity - Sabel, Joachim, 1962-; Saito, Mamoru (Studies in generative grammar, 2005)
This book deals with the syntax of the free word order phenomenon in a wide range of languages - in particular, German, Japanese, Kannada, Malayalam, Serbo-Croatian, Tagalog, Tongan, and Turkish - in some of which the phenomenon was previously unstudied. The different articles offer ways of analyzing free word order under minimalist assumptions, with respect to the question of how it is acquired, how a typology of free word order languages can be derived, and in connection with its relatedness to information structural factors.